THE INFLUENCE OF COMPETENCE, QUALITY OF WORK LIFE ON PERFORMANCE OF EMPLOYEES OF THE FINANCIAL AND ASSET MANAGEMENT AGENCY JEMBER DISTRICT AREA THROUGH ORGANIZATIONAL CITIZENSHIP BEHAVIOUR AS AN INTERVENING VARIABLE - Wicaksono, Wahyu Wisudo; Setyowati, Trias; Herlambang, Toni (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: This study aims to test and analyze the effect of competence and quality of work of life on the performance of employees of the financial management and regional assets agency of Jember Regency through organizational citizenship behavior (OCB) as an intervening variable. Method: The research involved 80 respondents, and data were collected through questionnaire distribution. The analysis was conducted using inner model analysis and outer model analysis. Results: The findings indicate that competence has a significant positive effect on OCB. Quality of Work Life also has a significant positive effect on OCB. Furthermore, competence significantly positively affects employee performance, and Quality of Work Life also significantly positively affects employee performance. Additionally, OCB has a significant positive effect on employee performance. OCB is proven to mediate the effect of competence on employee performance and the influence of Quality of Work Life on employee performance. Novelty: This study highlights the mediating role of OCB in the relationship between competence, Quality of Work Life, and employee performance, providing deeper insights into human resource management in the financial management and regional assets agency of Jember Regency.